Cryptocurrency (Mata Uang Digital) Sebagai Alat Pembayaran Dalam Transaksi Perdagangan Elektronik (E-Commerce) - I Putu Suwantara; I Made Aditya Mantara Putra (Fakultas Hukum, Universitas Warmadewa, 2025)
The advancement of digital technology has led to the emergence of virtual currencies, notably cryptocurrency, which are increasingly used as a means of payment in electronic commerce (e-commerce) transactions. Although gaining popularity among businesses and the public, the use of cryptocurrency as a payment method is not yet legally recognized in Indonesia. Law Number 7 of 2011 on Currency stipulates that the Rupiah is the only legal tender within the territory of the Republic of Indonesia. This study aims to examine the legality of cryptocurrency in e-commerce transactions and the legal protection available for businesses that use it. The research employs a normative juridical method with statutory and conceptual approaches. The findings indicate that although cryptocurrency has been acknowledged as a tradable commodity on futures exchanges through Bappebti regulations, it is not recognized as an official payment instrument. This creates legal uncertainty and potential legal risks for business actors. Therefore, more specific and integrated regulation is urgently needed to legally govern the use of cryptocurrency in Indonesia, in order to ensure legal certainty, consumer protection, and prevent misuse in digital economic activities.